2014
DOI: 10.2215/cjn.05410513
|View full text |Cite
|
Sign up to set email alerts
|

Readmission within 30 days of Hospital Discharge among Children Receiving Chronic Dialysis

Abstract: Background and objectives The hospital admission rate for children receiving chronic dialysis has been increasing over the last decade. Approximately one third of patients with ESRD age 0-19 years are readmitted to the hospital within 30 days of discharge. The objective of this study was to examine hospital readmissions among a cohort of children receiving chronic dialysis to identify factors associated with higher rates of 30-day readmission.Design, settings, participants, & measurements A retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The overall readmission rate in PD patients within our study is similar to readmission rates reported by others: 25% in a pediatric U.S. PD population, and 19.8% in readmission due to infection-related hospitalizations in a Canadian population (7,9). Of note, our estimate is nearly twice that of a recent study focusing on the readmission burden in the U.S. PD population (15%) (15).…”
Section: Discussionsupporting
confidence: 89%
“…The overall readmission rate in PD patients within our study is similar to readmission rates reported by others: 25% in a pediatric U.S. PD population, and 19.8% in readmission due to infection-related hospitalizations in a Canadian population (7,9). Of note, our estimate is nearly twice that of a recent study focusing on the readmission burden in the U.S. PD population (15%) (15).…”
Section: Discussionsupporting
confidence: 89%
“…We identified that length of index hospital stay was an independent risk factor of 30-day unexpected rehospitalization. Patients with longer hospital stay always presented with more severe or complicated disease condition during index admission [ 26 ]. Such complex condition not only prolonged their index hospital care, but also made them more vulnerable to an unexpected rehospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focusing on general pediatric diseases have demonstrated that the readmission rate is higher in young patients and in those born preterm. 10,40,43,47 Compared with older children, these groups of patients are considered more vulnerable to complications, resulting in a relatively lower threshold to admit these patients and, therefore, higher readmission rates. Furthermore, these patients have several associated conditions that might require a multidisciplinary team approach to determine physiological stability before discharge placement.…”
Section: Discussionmentioning
confidence: 99%